2021
DOI: 10.1186/s42358-021-00204-5
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic implications, incidence, and outcomes of COVID-19 in autoimmune inflammatory joint diseases and autoinflammatory disorders

Abstract: As the coronavirus disease 2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) continues to spread rapidly, there are still many unresolved questions of how this virus would impact on autoimmune inflammatory joint diseases and autoinflammatory disorders. The main aim of this paper is to describe the main studies focusing their attention on COVID-19 incidence and outcomes of rheumatoid arthritis (RA), spondylarthritis (SpA), and autoinflammatory disease cohorts. We al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 80 publications
4
14
0
2
Order By: Relevance
“…However, studies have also reported no influence from anti-rheumatic drugs on risk of severe COVID-19 outcomes, although the accuracy of data for partial drugs was unstable [ 45 , 46 ]. In more details, it has been suggested that no substantial risk was detected csDMARDS [ 42 ] as we show.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…However, studies have also reported no influence from anti-rheumatic drugs on risk of severe COVID-19 outcomes, although the accuracy of data for partial drugs was unstable [ 45 , 46 ]. In more details, it has been suggested that no substantial risk was detected csDMARDS [ 42 ] as we show.…”
Section: Discussionsupporting
confidence: 66%
“…Both csDMARDs and bDMARDs linked with a higher risk of serious infections [ 41 ]. These drugs target key molecules involved in the immune response against infectious antigens and therefore may increase susceptibility to viruses and bacteria [ 42 ]. It has been confirmed in multiple studies, in which medium-dose and above (> 5mg) glucocorticoids (GC) have increased risk of hospitalization in rheumatic patients who develop COVID-19 [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our study confirms that immunosuppressant therapy (in particular band ts-DMARDs) seems not to be associated with higher risk of COVID-19 complications nor with severe prognosis. These findings are consistent with published data about the safety of the aforementioned therapies [21,[35][36][37], particularly referring to the association between anti-TNF treatments, and both the reduced odds of hospitalization and the lower rate of complications during COVID-19, since also in our cohort the most used biologic drugs were anti-TNFs (24/37). Interestingly, the hospitalization rate in our cohort of RMD patients is even lower compared to the study performed by Gianfrancesco et al (24% vs. 46%, respectively) [21].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, our study confirms that immunosuppressant therapy (in particular band ts-DMARDs) seems not to be associated with higher risk of COVID-19 complications nor with severe prognosis. These findings are consistent with published data about the safety of the aforementioned therapies [21,[35][36][37], particularly referring to the association between anti-TNF treatments, and both the reduced odds of hospitalization and the lower…”
Section: Discussionsupporting
confidence: 92%
“…The impact of the global health crisis due to the virus Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2)—the causative pathogen of the coronavirus disease 2019 (COVID-19)—has begun to alter with the timely development, approval and administration of vaccines [ 1 ]. Although SARS-CoV-2 infection primarily targets the respiratory system [ [2] , [3] , [4] , [5] , [6] ], it is now recognised that the infection and its clinical manifestations are systemic [ [7] , [8] , [9] , [10] , [11] , [12] ], and also affecting the cardiovascular system of adults and children [ [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] ]. Cardiac complications of variable severity with acute and long-term sequelae are now known to include acute myocardial injury, arrhythmias, vasculitis and endothelial dysfunction, thrombosis, myocardial fibrosis, and myocarditis [ [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] ].…”
mentioning
confidence: 99%